Reconstruction of porous media pore structure and simulation effect analysis of multi-index based on SNESIM algorithm - Qing Xie; Jiaqi Gao; Xiaochuang Ye; Jia Li; Yifei Song; Siwen Hu (Scientific Reports)
Abstract The pore structure of porous media directly affects its permeability characteristics and fluid flow properties, making the accurate reconstruction of these structures of great significance. In recent years, multi-point statistics (MPS) methods have been widely used in pore structure modeling. Among them, the SNESIM algorithm, as an advanced MPS technique, has been extensively applied in the study of porous media pore structures. This paper aims to investigate the use of the SNESIM algorithm for reconstructing pore structures on 2D core slices with varying porosities, all taken from the same core. It also analyzes the effectiveness, limitations, and applicable conditions of the algorithm. This study utilizes CT scan images to construct digital core technology and applies the SNESIM algorithm to reconstruct pore structures of core slices with different porosities. By analyzing performance parameters such as porosity, pore throat ratio, average grain radius, coordination number, and permeability, the study shows that the reconstructed images(RI) from most samples maintain a trend similar to that of the training images(TI), demonstrating the good applicability and reliability of the SNESIM algorithm in pore structure reconstruction. However, the core slices used in this study were all taken from the same core. Effectively transferring the pore structures from the 2D plane to the 3D pore space and restoring the pore structures to the greatest extent still requires further research. In particular, when dealing with complex pore structures, the accuracy and performance of the SNESIM algorithm need further improvement. Future research will focus on optimizing the algorithm to handle more diverse pore structures and exploring 3D reconstruction methods to more comprehensively describe and analyze the pore characteristics in actual porous media.